Cascade enzymatic cleavage of the β-O-4 linkage in a lignin model compound. Issue 7 (23rd November 2015) - Rosini, Elena; Allegretti, Chiara; Melis, Roberta; Cerioli, Lorenzo; Conti, Gianluca; Pollegioni, Loredano; D'Arrigo, Paola
Abstract : The optimized Lig enzymatic system reached the full bioconversion of a racemic mixture of GGE, a lignin model compound. Abstract : The β-O-4 aryl ether linkages represent about 50% of all ethers in various lignins. At least three enzymatic steps are required to break them down: a NAD + -dependent C-α dehydrogenase (such as LigD and L), a glutathione lyase that releases guaiacol ( i.e., a β-etherase such as LigE and F), and a glutathione-dependent lyase ( i.e., LigG). In this work the LigD, L, E, F, and G from Sphingobium sp. SYK-6 were overexpressed in E. coli and purified with high yields. After characterizing the stability and kinetic properties of LigD and L on the lignin model compound GGE (1-(4-hydroxy-3-methoxyphenyl)-2-(2-methoxyphenoxy)propane-1, 3-diol) and the thermostability of all five recombinant Lig enzymes, the experimental conditions for GGE bioconversion could be optimized ( i.e., pH 9.0, 25 °C, ≈0.1 mg mL −1 of each enzyme, and 0.5 mM racemic substrate). Under optimal conditions, and by recycling NADH using thel -lactate dehydrogenase–pyruvate system, GGE was fully converted into the final products 3-hydroxy-1-(4-hydroxy-3-methoxyphenyl)propan-1-one and guaiacol in <2 hours. Differently from what was previously reported, this result and chiral HPLC analyses demonstrated that LigG catalyzes the glutathione-dependent thioether cleavage of both β( R )- and β( S )-isomer intermediates produced by LigE and LigF β-etherases: this allowed, for the first time, reaching 100% conversion of GGE. Altogether, the recombinant five-enzyme Lig system represents a component well suited for a multienzymatic process, comprising well-known ligninolytic activities (such as peroxidases and laccases), devoted to transforming selected lignins into aromatic compounds as an alternative to the oil source.